Risk of Colorectal Cancer in Ulcerative Colitis Patients: A Systematic Review and Meta-Analysis - Qing Zhou; Zhao-Feng Shen; Ben-sheng Wu; Cheng-biao Xu; Zhong-qi He; Tuo Chen; Hong-tao Shang; Chao-fan Xie; Si-yi Huang; Yu-gen Chen; Hai-bo Chen; Shu-tang Han (Gastroenterology Research and Practice)
Background. Ulcerative colitis (UC) patients have an increased risk for the development of colorectal cancer (CRC). Our aim was to assess the risk of CRC in UC patients compared with disease extent, disease duration, and geographic variation. Methods. In this systematic review and meta-analysis, we searched PubMed, scientific meetings, and the bibliographies of identified articles, with English language restrictions for studies published from 1988 to 2018, and assessed the risk of CRC in UC patients. Patients with Crohn’s disease, family history of CRC, and colorectal adenomatous polyp (CAP) were excluded from this research. The study was registered with PROSPERO, number CRD42018102213. Findings. We included 58 studies that included 267566 UC patients. Extensive UC and left-sided UC had a higher risk of CRC than proctitis UC. Geography also played a role in UC-associated CRC development. The time of malignant transformation in Asian UC patients started after 10-20 years of this disease duration. North American UC-associated CRC patients significantly increased in more than 30 years of this disease duration. Conclusion. In a systematic review of the literature, we found that disease extent, disease duration, and geography were strong, independent risk factors in UC-associated CRC development.